Bioactive poly(2-oxazoline)-based nanomaterials bearing arylalkylamine and benzamide motifs possess intrinsic radical trapping and anti-ferroptosis properties. (15th March 2023) - Morrow, Joshua P.; Pizzi, David; Mazrad, Zihnil A. I.; Bush, Ashley I.; Kempe, Kristian
Abstract : Poly((2-methyl-2-oxazoline)-grad-(2-phenyl-2-oxazoline)) and core-crosslinked micelles thereof are capable of inhibiting ferroptosis, a non-apoptotic iron-induced cell death mechanism. Abstract : Radical trapping agents such as Ferrostatin-1 (Fer-1) are capable of rescuing cells from ferroptosis, an iron-dependent form of cell death. Previously, poly(2-oxazoline)-Fer-1 (POx-Fer-1) conjugates were reported, which possess increased water-solubility and remain active after covalent conjugation of Fer-1. In this study, we break down the structural and functional layers of POx-Fer-1 conjugates and reveal that drug-free POx containing arylalkylamine and benzamide motifs show anti-ferroptosis properties. Intriguingly, even the basic construct poly(2-methyl-2-oxazoline-grad-2-phenyl-2-oxazoline) P(MeOx-grad-PhOx) was found to be active. Therefore, P(MeOx-grad-PhOx) of varying compositions were prepared, characterized by 1 H NMR spectroscopy and size exclusion chromatography and investigated with regard to their self-assembly in aqueous solution and activity in an in vitro ferroptosis model. These findings were further explored for the design of defined and bioactive core-crosslinked micelles with intrinsic anti-ferroptosis behaviour. Cellular interaction studies involving C11 -BODIPY assays and confocal microscopy investigations revealed lysosomal processing of the nanomaterials and perturbation of ferroptotic cell death through reducing lipid-peroxidation. This study highlights new drug/cargo-free anti-ferroptotic nanomaterials as proof of concept that hold potential for therapy of ferroptosis-associated diseases and highlights the role of nanocarriers in a therapeutic context.